Environments for the Implementation of Islamic Education - Kadar Risman; Halid Hanafi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
Children are a gift given by Allah SWT to parents who at the time of birth are in a state of nature or purity and further development in the development of their personality needs to be guided properly following the guidance of Islamic teachings. The environment has a big influence on the child's education process. This study aims to get an explanation of the description of the educational environment in Islam and how it is implemented according to the foundation of Islamic education. The research method used is Library Research. The data sources used come from scientific journals, reference books according to the field of study. The data analysis used in this study is content analysis, the data verification technique used is a descriptive analysis approach. In general, the educational environment where the educational process takes place is divided into three, namely; Formal, Informal, Non-formal. The implementation of these three environments can be carried out in the family, school and community environment. The Islamic education environment is the place where the process of instilling Islamic values takes place in students whose environment consists of the school family environment and the community environment.